Endoplasmic reticulum membrane‐bound MoSec62 is involved in the suppression of rice immunity and is essential for the pathogenicity of Magnaporthe oryzae. (29th March 2016) - Zhou, Zhuangzhi; Pang, Zhiqian; Li, Guihua; Lin, Chunhua; Wang, Jing; Lv, Qiming; He, Chaozu; Zhu, Lihuang
Summary: Pathogen‐associated molecular pattern (PAMP)‐triggered immunity (PTI) constitutes the first line of plant inducible immunity. As an important step of plant colonization, phytopathogens have to suppress PTI, and secreted effectors are therefore co‐evolved and deployed. In this study, we characterized the function of MoSec62 of Magnaporthe oryzae, the causal agent of the destructive rice blast. MoSec62 encodes a homologue of Sec62p, a yeast endoplasmic reticulum (ER) membrane transporter for precursors of secretory proteins. We showed that a T‐DNA insertion into the promoter region of MoSec62, causing a disturbance to the up‐regulation of MoSec62 expression during blast invasion, resulted in a complete loss of blast virulence of the mutant, M1575. Both 3, 3′‐diaminobenzidine (DAB) staining of the infected rice leaves and expression analysis revealed that the infectious attempt by the mutant led to strong defence responses of rice. Consistently, in transcriptomic analysis of rice leaves subject to blast inoculation, a battery of defence responses was found to be induced exclusively on M1575 challenge. For further exploration, we tested the pathogenicity on a highly susceptible rice variety and detected the accumulation of Slp1, a known PTI suppressor. Both results suggested that the mutant most likely failed to overcome rice PTI. In addition, we showed that MoSec62 was able to rescue the thermosensitivity of a yeast Δsec62, and the MoSec62‐GFP fusion was co‐localized to the ER membrane, both suggesting the conservation of Sec62 homologues. In conclusion, our data indicate that MoSec62, probably as an ER membrane transporter, plays an essential role in antagonizing rice defence at the early stages of blast invasion.